Students’ Perspective on the Use of Short Video in Social Media for English Language Learning - Baratha, Muhammad Isya Atsila; Madjid, Hilda Izzati; Feriyal (ICONELT, 2024)
The research purpose is to explore the student’s perspective on the utilization of short video in social media to learn English language. This research was qualitative descriptive research. In collecting data, the researcher used an open-ended questionnaire, which included 21 questions for the questionnaire. The participants were 31 basic-level students of MTsN 4 Surabaya, one of Islamic Junior High Schools in Surabaya. The findings show that through short videos in social media the students more easily understand the material as well as can enrich their vocabularies. Through the use of illustrations and many examples, the students are helpful in grabbing the explanation. In addition, short videos also offer a fun and interesting way of learning sufficiently.The perspectives of every participant vary and some responses are not suitable to their learning style. Aside from their learning style, the English language acquisition on short videos is inclined to the speaking skills.